PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN STMIK SINAR NUSANTARA SURAKARTA - Elistya Rimawati (STMIK Sinar Nusantara, 2016)
STMIK Sinar Nusantara Surakarta as the College of services should provide satisfaction to its customers. One of the direct customers is a student. Measurement of the influence of service quality on customer satisfaction needs to be done to determine the exact police specific to the variables associated with the quality of service. Measuring the influence of service quality to satisfaction done by using multiple regression analysis with random sampling of data. The results of the analysis of the quality of service that is reliable, the service is assured, tangible service are significant influence and positive impact on customer satisfaction. The service was responsive and empathetic service has no significant effect on customer satisfaction.Keywords: service that is reliable, service was responsive, service is assured, empathetic service, tangible service